Electrospun Mats Based on PVA/NaDDBS/CNx Nanocomposite for Electrochemical Sensing - Paloma Vilchis-León (MDPI AG, 2021)
This study presents a nanocomposite developed with PVA, multiwall carbon nanotubes (CNTs) doped with nitrogen, and NaDDBS, which change the electrical properties of the polymer and its viscosity to be used in electrospinning process for obtaining mats of nano/macro fibers. The proposed nanocomposite was characterized using Fourier transform-infrared and Raman spectroscopy techniques, confirming the presence of the CNxs immersed in the polymer. High-resolution transmission electron microscopy was used to obtain the micrographs that showed the characteristic interplanar distances of the multiwall CNT in the polymeric matrix, with values of 3.63 Å. Finally, the CNx mats were exposed to various aqueous solutions in a potentiostat to demonstrate the effectiveness of the nanofibers for electrochemical analysis. The CNx-induced changes in the electrical properties of the polymer were identified using cyclic voltammograms, while the electrochemical analysis revealed supercapacitor behavior.